Global Superconvergence Estimates of Finite Element Method for Schrödinger Equation (Journal of Computational Mathematics, 2021)
In this paper, we shall study the initial boundary value problem of Schrödinger equation. The second order gradient superconvergence estimates for the problem are obtained solving by linear finite elements.
Keywords: Finite element; superconvergence estimates; interpolation; Schrödinger equation.